Learning Process Management at PKBM RA Abata Mardhotillah Karawang - Suci Rokhmawati; Abdul Kosim; Kasja Eki Waluyo (Universitas Muhammadiyah Enrekang, 2022)
This study discusses the Management of the PKBM Learning Process in RA Mardhotillah Karawang. PKBM itself is categorized as a non-formal education unit that can provide educational services like other formal education. In addition, this study also aims to describe learning management in playgroups at RA Abata Mardhotillah Karawang. Based on these objectives, it can be translated back into specific objectives, namely to describe learning planning at RA Abata Mardhotillah Karawang, implementation of learning at RA Abata Mardhotillah Karawang, and evaluation of learning at RA Abata Mardhotillah Karawang, as well as factors that become obstacles and support in learning management as well as efforts to overcome the inhibiting factors in learning management. This data collection technique uses interview techniques, observation and documentation. The research method used is by using a qualitative descriptive research method. While data collection was done by using interview, observation, and documentation techniques.